Challenges and strategies of matrix effects using chromatography-mass spectrometry: An overview from research versus regulatory viewpoints - Raposo, Francisco; Barceló, Damià (TrAC, Trends in analytical chemistry (Regular ed.), 2021)
Matrix components of a sample can affect the quantitative measurement of the target analytes. This singularity is named “matrix effects” and should be considered for method validation procedure. Two main strategies to overcome matrix effects were suggested in the scientific literature: reducing the presence of components responsible for the effects and compensating the influence of matrix effects in the calibration methodology. It has been recommended that the best option to surpass matrix effects at research level is to establish a systematic optimization by the combination of approaches. On the other hand, from the method validation regulatory viewpoint, the information contained in the different method validation guidelines about matrix effects was uncommon. In fact, only in 54% of the evaluated regulatory documents the term matrix effects was mentioned explicitly in their contents. In addition, in the rest of the guidance documents addressing matrix effects, the subject was typically considered only superficially. [Display omitted] •Matrix effects are critical for validation of chromatography-mass spectrometry methods.•Detailed evaluation of matrix effects for method validation.•Discrepant information for matrix effects from research versus regulatory points of views.•Contradictory information about matrix effects among different method validation guidelines.